Persepsi Kontrol Perilaku dalam Niat Berhenti Mengonsumsi Minuman Beralkohol pada Mahasiswa di Surabaya - Zulfa Kevaladandra; Ira Nurmala (Jurnal Keperawatan Muhammadiyah, 2019)
Alcohol misuse problem has been a concern all around the world, especially among adolescent. Consume alcohol beverages might cause a several problem both physically and mentally, serious accident, and also an increase in criminality. This study was about to describe perceived behavioral control of individu which can effect someone’s intention to stop drinking alcohol. This study was a qualitative research using phenomenology approachment. The data was collected with in-depth interview technique. Informant in this study was about 7 people and was selected with snowball sampling. The result showed that all of the informant had a perceived behavioral control to support their intention not consumed alcohol beverages. There were 4 informants which had a positive perceived behavioral control whilst the rest of informants had a negative perceived behavioral control. In conclusion, perceived behavioral control may effect someone’s intention to stop drinking alcohol. In addition, peer education as a social support is needed to be an effort in controlling someone’s behavior to stop drinking alcohol beverages.